2009
DOI: 10.1111/j.1365-2567.2008.02906.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective human endothelial cell activation by chemokines as a guide to cell homing

Abstract: SummaryAn original model of organo-specific, immortalized and stabilized endothelial cell lines was used to delineate the part played by some chemokines (CCL21, CX3CL1, CCL5 and CXCL12) and their receptors in endothelium organo-specificity. Chemokine receptor expression and chemokine presentation were investigated on organo-specific human endothelial cell lines. Although the chemokines showed distinct binding patterns for the various endothelial cell lines, these were not correlated with the expression of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 37 publications
4
22
0
Order By: Relevance
“…In the presence of chemokine gradients, the α-chemokine, CXCL12, exhibits a polarized distribution in favor of the basolateral surface in resting HBMEC followed by redistribution to the apical surface upon cytokine stimulation, resulting in equal binding along the basal and apical surfaces [17]. In this respect it is interesting that the binding of chemokines to endothelial cells derived from different organs can vary greatly [28]. The differential binding of various chemokines to resting and cytokine-activated HBMEC may well reflect changes in the surface charge of endothelial cells and the chemical structure and distribution of glycosaminoglycans in the course of the inflammatory response [29].…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of chemokine gradients, the α-chemokine, CXCL12, exhibits a polarized distribution in favor of the basolateral surface in resting HBMEC followed by redistribution to the apical surface upon cytokine stimulation, resulting in equal binding along the basal and apical surfaces [17]. In this respect it is interesting that the binding of chemokines to endothelial cells derived from different organs can vary greatly [28]. The differential binding of various chemokines to resting and cytokine-activated HBMEC may well reflect changes in the surface charge of endothelial cells and the chemical structure and distribution of glycosaminoglycans in the course of the inflammatory response [29].…”
Section: Resultsmentioning
confidence: 99%
“…Both cancer cells and normal cells were used. The HSkMEC (Human Skin Microvascular Endothelial Cells) cell line was obtained from Cell Culture Collection of the IIET (Wroclaw, Poland) (Crola Da Silva et al 2009). The B16F0 mouse melanoma cancer cell line was obtained from the American Type Culture Collection (ATCC, USA).…”
Section: Characterisationmentioning
confidence: 99%
“…Previous studies have demonstrated that CCL21 is expressed by lymph node endothelial cells and functions as an endothelial cell growth factor (3). Expression of CCL21 is associated with formation of tertiary lymphoid tissue, a process called lymphoid neogenesis (4).…”
mentioning
confidence: 99%